A high order mesh-free method for buckling and post-buckling analysis of shells. (February 2019) - Fouaidi, Mustapha; Hamdaoui, Abdellah; Jamal, Mohammad; Braikat, Bouazza
Abstract: In this paper, a high order mesh-free method is investigated for buckling and post-buckling analysis of shells subjected to external loadings. This high order mesh-free method is built within the framework of the First Order Shear Deformation Theory (FOSDT) employing the Asymptotic Numerical Method (ANM) and the mesh-free collocation method. The strong form of nonlinear equations governing the equilibrium of these shells are derived by using the Collocation Scheme (CS) adopting the Total Lagrangian formulation (TL). The implementation of the boundary conditions is performed by the direct collocation method. Some benchmarks are considered to verify the ability and the accuracy of the used algorithm for investigating the buckling and post-buckling behavior of this type of structures. The obtained results are compared to those computed numerically by the same algorithm using the Finite Element Method (FEM) and to those of literature.